Transformation of Educational Management in Improving the Quality of Islamic Boarding Schools in Banten Province - Noviani, Lona; Qurtubi, Ahmad; Muslihah, Eneng (Journal of Social Science and Business Studies, 2024)
This study aims to analyze the impact of management transformation on the improvement of education quality in Islamic boarding schools in Banten Province. Management transformation, which includes the management of human resources, finance, curriculum, and facilities, can contribute to the enhancement of education quality, both in modern and traditional Islamic boarding schools. The research method used in this study is a quantitative approach with statistical analysis to examine the relationship between management transformation and the improvement of education quality. Data were collected through questionnaires with a sample size of 100 respondents, consisting of administrators and students of Islamic boarding schools in the Banten region. The results of the study indicate a significant impact of management transformation on the improvement of education quality in Islamic boarding schools. This study suggests that Islamic boarding school administrators should periodically implement management transformation as an effort to enhance education quality in line with the development of the times.